Reformulation of Nahwu for Non-Arabic Speakers: A Study of Aiman Amin Abdul Ghani's Views and Principles l I’adah Tanzim al-Mawad al-Nahwiyyah li al-Natiqin bigair al-‘Arabiyyah: Dirasah fi Ara’ wa Mabadi’ Aiman Amin Abdul Ghani - Muis, Muhsin; Hamid, M. Abdul; Chamidah, Dewi; Baklizi, Mai Khalied Mahmoud (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article presents the analysis of Aiman Amin Abdul Ghani's views on the reformulation of Nahwu (Arabic grammar) for non-native speakers. The focus of this analysis included how Aiman Amin Abdul Ghani developed a simplified Nahwu teaching method while retaining essential grammatical rules of the Arabic language. The complexity of Nahwu often poses challenges for Arabic learners without an Arabic background, and understanding Abdul Ghani's approach was expected to provide an effective pedagogical solution. Data sources for this study included direct interviews with Aiman Amin Abdul Ghani, in-depth analysis of his works such as An-Nahwu Al-Kafi, Al-Kafi fi Sharh Matn Al-Ajurumiyyah, and An-Nahwu Bayna Yadayk, as well as a literature review of relevant Nahwu teaching methods. Data were analyzed with interpretive and hermeneutic methods, aiming to identify Aiman Amin Abdul Ghani's unique contributions to the reformulation of Nahwu. The findings showed that while Aiman Amin Abdul Ghani concurred with earlier scholars about the complexity of Nahwu, he proposed a different approach by retaining all grammatical rules but arranging them in a systematic and gradual way to facilitate comprehension for non-native speakers. This article contributes to the development of Nahwu pedagogy and emphasizes the importance of integrating religious values in Arabic grammar reform.